2020
DOI: 10.3390/molecules25214904
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies towards the Identification of Novel Rhodopsin-Binding Compounds as Chemical Chaperones for Misfolded Opsins

Abstract: Accumulation of misfolded and mistrafficked rhodopsin on the endoplasmic reticulum of photoreceptor cells has a pivotal role in the pathogenesis of retinitis pigmentosa and a subset of Leber’s congenital amaurosis. One potential strategy to reduce rhodopsin misfolding and aggregation in these conditions is to use opsin-binding compounds as chemical chaperones for opsin. Such molecules have previously shown the ability to aid rhodopsin folding and proper trafficking to the outer cell membranes of photoreceptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Although P23H Rho can escape the ER quality control in vivo and traffic to the rod outer segments, insufficient regeneration of this mutant would diminish the supply of the functional receptor (Sakami et al 2011). Thus, the supplementation with small molecule chaperones that would enhance the chromophore regeneration rates and increase the structural stability and folding appears to be a valid approach to improve the fitness of RP mutants (Chen et al 2018; Behnen et al 2018; Pasqualetto et al 2020; Mattle et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although P23H Rho can escape the ER quality control in vivo and traffic to the rod outer segments, insufficient regeneration of this mutant would diminish the supply of the functional receptor (Sakami et al 2011). Thus, the supplementation with small molecule chaperones that would enhance the chromophore regeneration rates and increase the structural stability and folding appears to be a valid approach to improve the fitness of RP mutants (Chen et al 2018; Behnen et al 2018; Pasqualetto et al 2020; Mattle et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, targeting this mutant with stabilizing agents to prevent or slow down the progression of RP is a valid approach. Several recent studies showed that stabilization of the Rho mutants, including P23H Rho with retinoid‐based and non‐retinoid small molecules, improved the fitness of these Rho variants in vitro (Behnen et al 2018; Chen et al 2018; Mattle et al 2018; Pasqualetto et al 2020). In addition, we found that flavonoids positively modulate the stability of ligand‐free rod opsin and improve membrane targeting of P23H Rho in vitro (Ortega et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Current data suggest the pigment regeneration chemistry in lancelets is homologous that in vertebrates ( Albalat et al, 2012 , Poliakov et al, 2012 , Vopalensky et al, 2012 ). The chromophore covalently binds at position Lys 296 in all opsins ( Lamb, 2013 , Pasqualetto et al, 2020 ). Molecular fingerprinting of lancelets has identified a total of 21 opsin genes ( Pergner and Kozmik, 2017 ) which produce highly variable opsin proteins: this diversity is comparable to that in vertebrates.…”
Section: How To Make An Eye From Scratchmentioning
confidence: 99%
“…This hydrophobic area of the binding cleft acts as an essential recognition site for the ionone ring and for binding to this site, as confirmed by the ability of the shortened retinal derivative β-ionone (Figure 3), to competitively inhibit binding of 11-cis-retinal. β-Ionone binding however, which we previously investigated by molecular docking studies [15], does not induce any physiological effect on opsin trafficking [16][17][18]. Along with the binding of the endogenous ligand, the common structural features of 11-cis-retinal and different compounds known to competitively inhibit its binding to opsin were considered for the design of novel potential ligands for the orthosteric pocket, as depicted in Figure 3.…”
Section: Ligand-based Rational Design Of Novel Potential Opsin-bindin...mentioning
confidence: 99%
“…Finally, one last set of modified analogues were designed as derivatives of 11-cis-6mr-retinal, to maintain the terminal β-ionone portion and the function to target Lys296, mainly a aldehyde to form a covalent Schiff base bridge, while exploring different potential central cores between the two functionalities, such as a tetrahydroisoquinoline nucleus with a branched (15) or linear alkyl spacer (16a-b), or a piperidine nucleus with either an cyclic (17) or an unsaturated linear spacer (18). The newly designed analogues are shown in Figure 7, along with their predicted binding to the orthosteric pocket of rhodopsin crystal structure (PDB ID 1U19).…”
Section: Figurementioning
confidence: 99%